Comparative analysis of models of genetic and neuronal networks - Ogorelova, Diana; Sadyrbaev, Felix (Mathematical Modelling and Analysis, 2024)
The comparative analysis of systems of ordinary differential equations, modeling gene regulatory networks and neuronal networks, is provided. In focus of the study are asymptotical behavior of solutions, types of attractors. Emphasis is made on the chaotic behavior of solutions.